2015
DOI: 10.1016/j.vaccine.2014.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Cost analysis of routine immunisation in Zambia

Abstract: Total and unit costs, and government's contribution, were considerably higher than previous Zambian estimates and international benchmarks. These findings have substantial implications for planners, efficiency improvement and sustainable financing, particularly as new vaccines are introduced. Variations in immunisation costs at facility level warrant further statistical analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 11 publications
0
50
0
Order By: Relevance
“…Three sites were excluded due to unresolved inconsistencies. Data cleaning and standardization resulted in minor differences with earlier studies’ country-level results [ 8 11 ]. Datasets and related materials are available at www.immunizationeconomics.org and archived on Dataverse [ 19 ].…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…Three sites were excluded due to unresolved inconsistencies. Data cleaning and standardization resulted in minor differences with earlier studies’ country-level results [ 8 11 ]. Datasets and related materials are available at www.immunizationeconomics.org and archived on Dataverse [ 19 ].…”
Section: Methodsmentioning
confidence: 90%
“…The Expanded Program on Immunization Costing and Financing (EPIC) Project was designed to fill this knowledge gap, providing detailed data on routine immunization costs and financing in a large, representative sample of immunization sites in six countries (Benin, Ghana, Honduras, Moldova, Uganda, and Zambia) [ 7 ]. Information from these studies has already been used to improve information on unit costs [ 8 11 ], cost trends [ 12 , 13 ], and financing [ 14 , 15 ] within individual countries. We synthesized data from these country studies to create a unique pooled dataset of 316 sites to explore cross-country determinants of costs.…”
Section: Introductionmentioning
confidence: 99%
“…The EPIC studies collected information on service volume, costs and other characteristics for 319 sites providing routine immunization services in Benin, Ghana, Honduras, Moldova, Uganda, and Zambia during the 12month period January-December 2011 [22]. Data were collected through a series of country-level studies implemented during 2012-13 [25][26][27][28][29][30]. Sites were selected from a sampling frame consisting of public and NGO facilities providing routine immunization services, and data were collected using a standardized approach [31], to allow comparison and pooling of data across sites and settings.…”
Section: Data and Samplementioning
confidence: 99%
“…In addition, Geng et al (2017) and Schütte et al (2015) have demonstrated that program costs do not 29 scale linearly at a facility level and Ahanhanzo et al (2015) demonstrated that the size of a clinic is an 30 important cost driver. In this paper, we examine whether programmatic costs for supplementary 31 immunization activities (SIAs) demonstrate efficiencies of scale.…”
mentioning
confidence: 99%